PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA - Devinta Rizkia; M. Zainal Arifin, Rukmini Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study uses a Quasi Experimental research type. The purpose of this study was to determine the effect of implementing the Problem Based Learning model on mathematics learning outcomes. The subjects of this study were students in grades V - B and V - D of Elementary School Negeri Polisi 4 Bogor City consisting of 67 students, this study was conducted in the even semester of the 2024/2025 school year. Sampling was carried out using a purposive sampling technique. Data collection was carried out to obtain learning outcomes using pretest and posttest. Data analysis was carried out using the N - Gain test, Normality Test, and Homogeneity Test as prerequisite tests before conducting the Hypothesis Test (t-test). The average N-Gain score in the experimental class was 70 and the average N-Gain score in the control class was 65. Then the results of the hypothesis testing using the t-test obtained a count (2.22)> ttable (1.991714) for a significance of 5% so that H0 was rejected and Ha was accepted. Based on the results of the study, it can be concluded that there is an influence of Problem Based Learning on mathematics learning outcomes.